Les exportations canadiennes de marchandises : analyse préliminaire des mécanismes de survie - Lande, Eric (L'Actualité économique, 1983)
AbstractTheoretically, devaluations and revaluations should modify the market price of traded goods, but market structure may influence this process and have a determining impact on the nature of the trade flows. Market structure forces are shown to have the potential to be able to neutralize the expected effects of devaluations and revaluations on a country's trade balance. This is shown to be a Canadian problem dating back to the 18th and 19th centuries that may force Canada to look for other policies to influence the flow of traded goods and its balance of trade.